ELECTRIC AND ELASTIC PROPERTIES OF CONSOLIDATED TERRIGENOUS ROCKS OF CAMBRIAN PERIOD OF THE SOUTHERN SLOPE OF THE LVIV PALAEOZOIC TROUGH - Vyzhva, S.; Onyshchuk, V.; Onyshchuk І.; Reva М.; Shabatura О. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Paper concerned the research of elastic and electric properties of consolidated terrigenous rocks of Cambrian period of the southern slope of the Lviv Palaeozoic trough. The purpose of the research was to study the petrophysical parameters of the consolidated reservoir rocks (siltstones and sandstones), as the basis of the integrated analysis of their physical properties. The research looked at electric and elastic parameters of terrigenous rock samples, resistivity and formation resistivity factor, formation resistivity enlargement factor, velocities of the P-waves and interval (transit) time in atmospheric and reservoir conditions. Correlations between resistivity and formation resistivity factor, and between porosity and formation resistivity factor of consolidated rocks were established in atmospheric and reservoir conditions. The correlation between the resistivity and formation resistivity factor manifest itself in linear function. Physical modeling of reservoir conditions allows adapting the values of electrical parameters obtained in atmospheric conditions to parameters of rocks in reservoir conditions. Laboratory acoustic study of rock samples managed to establish correlations of: velocities of the P-waves and interval (transit) time with density and porosity in atmospheric conditions; velocities of the P-waves in atmospheric and reservoir conditions; velocities with porosity in reservoir conditions. The correlations between velocities of the P-waves in atmospheric and reservoir conditions for the studied rocks manifested itself in linear function. Physical modeling of reservoir conditions allows adapting the values of elastic parameters obtained in atmospheric conditions to parameters of rocks in reservoir conditions. The correlations between the electric and elastic properties and reservoir properties of siltstones and consolidated sandstones should be at the basis of preliminary interpretation of geophysical well logging on prospective areas of the southern slope of the Lviv Palaeozoic trough.